Edukasi Self-Concept melalui Komunikasi Antarpribadi Antara Orang Tua dengan Anak Pada Kegiatan Pengabdian “Hayu Urang Ngobrol, Dak...” - Murtanti Putri, Dianingtyas (Indonesian Journal for Social Responsibility, 2020)
Being a parent is not an easy task, especially if parents do not have enough stock to educate children. One of parenting that is intended is wrong parenting, will make the process of growth and development in children both psychologically and mentally will form a negative self-concept, so that it will affect self-esteem, self-efficacy is also negative. The lack of parenting knowledge possessed by parents to educate their children is also one of the main obstacles in the process. The Community Service (PKM) activity this time was carried out in the village of Karya Mekar, Cariu District, Bogor Regency, where social environmental factors, economic status, and the wrong model of parenting were handed downd to their successors. Also, his parents educational background was only completed by junior high school (SMP), some elementary schools (SD) only, they ended by continuing to live by getting married at a young age of 22-35 years. The purpose of service activities is to provide an understanding of the role of interpersonal communication in the process of forming self-concepts. The method of implementation is carried out in the form of parenting education, which is packaged with interactive experience sharing, here will also involve students to interpret the material using local languages, so that participants can understand. The results of the activity show that participants understand the packaging of messages from the basic theory of communication 5W + 1H to do during the interaction of communication with their children. Furthermore, participants are provided with knowledge on how to create a conducive communication climate with children to create mutual respect by avoid destructive sentence that can have an impact on their self-concept, self-esteem, self-efficacy.